STRATEGI PENGEMBANGAN SDM PADA PEMERINTAH DESA UNTUK MENCAPAI SDGS DESA - Nina Yanti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to find out the existing conditions of human resource development in the village government in North Tambusai sub-district, Rokan Hulu district; and how to prepare a human resource development strategy for the village government in North Tambusai sub-district, Rokan Hulu district using SWOT analysis. The theory used in this research is SWOT Analysis according to Freddy Rangkuti (2016). This research is a qualitative type of research. Research subjects were determined using purposive sampling to search for and explore data and information related to village government human resource development. Meanwhile, the data collection techniques used were observation, interviews and documentation. The data analysis used is data reduction, data presentation, and drawing conclusions. The results of this research show that the results of the SWOT analysis are in quadrant I which produces an aggressive strategy (SO). The recommended strategy is firstly utilizing the existence of human resources in the computer sector, secondly utilizing village funds and village government human resources, thirdly providing special training for staff and village officials through the community empowerment and village government service (DPMPD) on a regular and comprehensive basis, providing special training for staff and village officials through DPMPD periodically and comprehensively. Fourth, add and utilize village assistants in fostering the implementation of cooperation between villages through BKAD.